2001
DOI: 10.7326/0003-4819-135-7-200110020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Durable Treatment-Free Remission after High-Dose Cyclophosphamide Therapy for Previously Untreated Severe Aplastic Anemia

Abstract: High-dose cyclophosphamide therapy without bone marrow transplantation produces durable treatment-free remission in severe aplastic anemia. This approach deserves further study in patients with severe aplastic anemia who are not suitable candidates for allogeneic bone marrow transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 24 publications
1
74
0
1
Order By: Relevance
“…10 However, in recent years, the percentage of patients receiving singleagent HD cyclophosphamide up to 7 g/m 2 or 200 mg/kg experiencing cardiotoxicity has diminished to nearly zero with the adoption of multifractionated schedule of administration. 4,5,[7][8][9]25 Available evidence indicates that singleagent HD cyclophosphamide-associated cardiac toxicity is dose and schedule dependent, and it is not related to the cumulative drug dose. 13,16,21 No pharmacokinetic parameter has been consistently associated with cardiotoxicity, although a significant inverse association between a reduced HD cyclophosphamide area under the curve (AUC) (ie accelerated clearance due to an increased conversion to active metabolites) and cardiotoxicity was found in three independent studies, 17,26,27 but not confirmed in a larger one.…”
Section: Cardiac Toxicity Due To Conditioning Regimenmentioning
confidence: 99%
See 2 more Smart Citations
“…10 However, in recent years, the percentage of patients receiving singleagent HD cyclophosphamide up to 7 g/m 2 or 200 mg/kg experiencing cardiotoxicity has diminished to nearly zero with the adoption of multifractionated schedule of administration. 4,5,[7][8][9]25 Available evidence indicates that singleagent HD cyclophosphamide-associated cardiac toxicity is dose and schedule dependent, and it is not related to the cumulative drug dose. 13,16,21 No pharmacokinetic parameter has been consistently associated with cardiotoxicity, although a significant inverse association between a reduced HD cyclophosphamide area under the curve (AUC) (ie accelerated clearance due to an increased conversion to active metabolites) and cardiotoxicity was found in three independent studies, 17,26,27 but not confirmed in a larger one.…”
Section: Cardiac Toxicity Due To Conditioning Regimenmentioning
confidence: 99%
“…Total dose pmaximum-tolerated dose as single agent 4,5,[7][8][9]25 Schedule of administration Adopt the least cardiotoxic schedule (eg multifractionated schedule for HD cyclophosphamide) 4,5,[7][8][9]25 Concomitant administration of other chemotherapeutic agents Avoid reportedly cardiotoxic associations or treatment schedules 10,12,14,15,[39][40][41][42] History of radiation therapy to the mediastinum or left chest wall…”
Section: Dosagementioning
confidence: 99%
See 1 more Smart Citation
“…High-dose immunoablative cyclophosphamide alone has led to long-term remissions in aplastic anemia (15,16) and other autoimmune disorders (17). The unique pharmacology of high-dose cyclophosphamide is responsible for its ability to induce maximal immunosuppression without myeloablation.…”
mentioning
confidence: 99%
“…All four patients with marrow trilineage dysplasia exhibited neoplastic progression. Patients 16-32 (Table 1) met clinical criteria, 15 and were treated, for AA: 10 with high-dose cyclophosphamide, 18,19 four with immunosuppressive therapy (antithymocyte globulin and/or cyclosporine), 20 and three with allogeneic transplantation after high-dose cyclophosphamide conditioning. 21 None of these 17 patients has shown any evidence of neoplastic progression, and only two have died, both ( Table 1, Patients 28 and 29) with refractory neutropenia and infection while on immunosupporessive therapy.…”
Section: Resultsmentioning
confidence: 99%